2009
DOI: 10.1007/s12011-009-8320-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride-Induced Oxidative Stress in Rat’s Brain and Its Amelioration by Buffalo (Bubalus bubalis) Pineal Proteins and Melatonin

Abstract: Fluoride (F) becomes toxic at higher doses and induces some adverse effects on various organs, including brain. The mechanisms underlying the neurotoxicity caused by excess fluoride still remain unknown. The aims of this study were to examine F-induced oxidative stress (OS) and role of melatonin (MEL) and buffalo pineal proteins (PP) against possible F-induced OS in brain of rats. The 24 rats were taken in present study and were divided into four groups: control, F, F + PP, and F + MEL. The F group was given 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 34 publications
4
40
1
Order By: Relevance
“…We also observed that fluoride toxicity increased lipid peroxidation in brain tissues which may explain the mechanism of action of this toxicity (Nabavi et al 2012a). Others have also shown that fluoride intoxication leads to irregular changes in cellular mechanisms of brain cells (Bharti and Srivastava 2009).…”
supporting
confidence: 59%
“…We also observed that fluoride toxicity increased lipid peroxidation in brain tissues which may explain the mechanism of action of this toxicity (Nabavi et al 2012a). Others have also shown that fluoride intoxication leads to irregular changes in cellular mechanisms of brain cells (Bharti and Srivastava 2009).…”
supporting
confidence: 59%
“…Therefore, these findings support the hypothesis of protecting role of buffalo pineal proteins against arsenic-induced oxidative stress through its antioxidant properties and also find agreement with earlier findings of b [15] about free radical scavenging ability of pineal proteins.…”
Section: Discussionsupporting
confidence: 92%
“…However, earlier laboratory findings revealed that, these buffalo PP and peptides have certain physiological functions viz. immunopotentiation by Ramasamy, 2006 [12], heat stress by Sejian, 2006 [13], amelioration of fluoride-induced OS and apoptosis by Bharti, 2008 [14] and b [15]. These findings suggest the test for protecting role of PP against As-induced OS in kidney and blood.…”
Section: Introductionmentioning
confidence: 99%
“…Group one served as control, while the groups two and three were exposed to subchronic concentrations of 50 mg L -1 and 100 mg L -1 fl uoride in the form of sodium fl uoride through drinking water for 7 weeks. Water exposure mimicked epidemiological exposure and the concentrations were chosen based on studies of fl uoride-induced toxicity (12)(13)(14)(15).…”
Section: Animals and Treatmentmentioning
confidence: 99%